2009
DOI: 10.1088/0031-9155/54/4/004
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of induced radio-frequency electromagnetic fields in various anatomical human body models

Abstract: The reference levels for testing compliance of human exposure with radio-frequency (RF) safety limits have been derived from very simplified models of the human. In order to validate these findings for anatomical models, we investigated the absorption characteristics for various anatomies ranging from 6 year old child to large adult male by numerical modeling. We address the exposure to plane-waves incident from all major six sides of the humans with two orthogonal polarizations each. Worst-case scattered fiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
52
0
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(64 citation statements)
references
References 20 publications
9
52
0
3
Order By: Relevance
“…Hence, the uncertainty is the same as the one already investigated in previous studies [Findlay et al, 2006;Kühn et al, 2009;Bakker et al, 2010;Vermeeren et al, 2010]. Because the selected FDTD settings are similar and for some parameters even better than in the referenced papers, the estimated uncertainty is not larger than the overall uncertainty presented in these studies.…”
Section: Uncertainty On the Allowed Powermentioning
confidence: 55%
“…Hence, the uncertainty is the same as the one already investigated in previous studies [Findlay et al, 2006;Kühn et al, 2009;Bakker et al, 2010;Vermeeren et al, 2010]. Because the selected FDTD settings are similar and for some parameters even better than in the referenced papers, the estimated uncertainty is not larger than the overall uncertainty presented in these studies.…”
Section: Uncertainty On the Allowed Powermentioning
confidence: 55%
“…Due to averaging, no (local) negative values of temperature changes were found anymore. However, within the body the ratio 10 10 g g T SAR  still varied considerably. It exhibited a span of almost two orders of magnitudes reaching from 0.11 …”
Section: Figure 2 Region-specific Voxel-values δT Over Sar At the Chmentioning
confidence: 99%
“…In the meanwhile, progress in numerical simulation and digital anatomical modeling allowed demonstrating that RF EMF reference values are not conservative enough to justify presumption of conformity with basic restrictions in any case. Studies reported up to 45% excess of basic restrictions at exposure scenarios of persons with small body height such as children or undersized adults [7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the deterministic approach for studying exposure [11,12] that misses the stochastic aspect of the exposition conditions, statistical study of human exposure in a realistic environment is a domain of research that had few achievements. In [13] a stochastic approach is developed based on polynomial chaos in order to calculate the whole body SAR distribution induced by a incident parameter distribution as the angle of incidence of the waves.…”
Section: Introductionmentioning
confidence: 99%
“…In [11,12], body models are exposed to deterministic channel models. Even if these studies give a good indication of the level of exposure by calculating the SAR, these studies avoid the stochastic aspect of exposure.…”
Section: Introductionmentioning
confidence: 99%